2008
DOI: 10.1021/jm801205x
|View full text |Cite
|
Sign up to set email alerts
|

Highly Potent 4-Amino-indolo[2,3-c]azepin-3-one-Containing Somatostatin Mimetics with a Range of sst Receptor Selectivities

Abstract: The synthesis, biological evaluation, and conformational analysis of 4-amino-indolo[2,3-c]azepin-3-one (Aia)-containing SRIF mimetics are reported. Different subtype selectivities are observed depending on the N- and C-terminal substituents of the D-Aia-Lys dipeptide mimetic. An sst(5)-selective analogue with subnanomolar binding affinity was obtained that is the most potent agonist reported to date. A nonselective mimetic with high potency was also identified. This study allows a better definition of the bioa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…7,86,87 Unlike most of the literature on SRIF inhibitors that focuses on the β-turn backbone conformation of somatostatin, Tourweá nd co-workers investigated the importance of the side chain orientation of the D-Trp-Lys residues. 88,89 The design of these somatostatin peptidomimetics was based on the constrained Trp residues D-and L-Aia (104−108, Figure 19). Initially, D-Aia was introduced in the linear tetrapeptide 104 that contains the four essential side chains for sst receptor binding to provide compound 105.…”
Section: ■ Somatostatinmentioning
confidence: 99%
See 3 more Smart Citations
“…7,86,87 Unlike most of the literature on SRIF inhibitors that focuses on the β-turn backbone conformation of somatostatin, Tourweá nd co-workers investigated the importance of the side chain orientation of the D-Trp-Lys residues. 88,89 The design of these somatostatin peptidomimetics was based on the constrained Trp residues D-and L-Aia (104−108, Figure 19). Initially, D-Aia was introduced in the linear tetrapeptide 104 that contains the four essential side chains for sst receptor binding to provide compound 105.…”
Section: ■ Somatostatinmentioning
confidence: 99%
“…Analogue 110 on the other hand can be considered a broad spectrum sst ligand that binds to all subtypes in the nanomolar to subnanomolar range. 89 The authors thus concluded that the D-Aia-Lys dipeptide represents a universally recognized sst 1−5 pharmacophore. Despite the fact that the Aia scaffold prefers extended conformations rather than turn conformations, 58 it displays the ability to adopt trans or gauche side chain orientations.…”
Section: ■ Somatostatinmentioning
confidence: 99%
See 2 more Smart Citations
“…S5) and two agonists (27) (Fig. S6) to all five candidate structures (InactiveConf1, InactiveConf2, InactiveConf3, ActiveConf1, and ActiveConf2).…”
Section: Ligand Binding Studiesmentioning
confidence: 99%